2020
DOI: 10.1371/journal.pone.0241218
|View full text |Cite
|
Sign up to set email alerts
|

Repeated dermal application of the common preservative methylisothiazolinone triggers local inflammation, T cell influx, and prolonged mast cell-dependent tactile sensitivity in mice

Abstract: Occupational exposure to toxic chemicals increases the risk of developing localized provoked vulvodynia—a prevalent, yet poorly understood, chronic condition characterized by sensitivity to touch and pressure, and accumulation of mast cells in painful tissues. Here, we topically sensitized female ND4 Swiss mice to the common household and industrial preservative methylisothiazolinone (MI) and subsequently challenged them daily with MI or acetone and olive oil vehicle on the labiar skin. MI-challenged mice deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…In a follow-up study, repeated daily MI exposures for 10 days on the labial skin of previously sensitized mice resulted in mast cell accumulation and remarkably persistent tactile sensitivity for up to 70 days, long past the resolution of overt inflammation indicating possible central sensitization of the nervous system. Intraperitoneal treatment with imatinib, which targets protein kinase c-Kit expressed on mast cells, prevented mast cell accumulation and abrogated tactile sensitivity ( Kline et al., 2020 ). We derived vaginal fibroblast lines from sensitized mice exposed to 10 applications of MI or saline vehicle in the vaginal canal; fibroblasts derived from MI-challenged canals produced higher levels of IL-6 compared to those derived from saline-challenged canals when exposed to bacterial lipopolysaccharides or zymosan in vitro , mirroring the behavior of fibroblasts derived from vulvodynia patients ( Blum et al., 2020 ).…”
Section: Immune Responses To Common Environmental Toxins May Trigger ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In a follow-up study, repeated daily MI exposures for 10 days on the labial skin of previously sensitized mice resulted in mast cell accumulation and remarkably persistent tactile sensitivity for up to 70 days, long past the resolution of overt inflammation indicating possible central sensitization of the nervous system. Intraperitoneal treatment with imatinib, which targets protein kinase c-Kit expressed on mast cells, prevented mast cell accumulation and abrogated tactile sensitivity ( Kline et al., 2020 ). We derived vaginal fibroblast lines from sensitized mice exposed to 10 applications of MI or saline vehicle in the vaginal canal; fibroblasts derived from MI-challenged canals produced higher levels of IL-6 compared to those derived from saline-challenged canals when exposed to bacterial lipopolysaccharides or zymosan in vitro , mirroring the behavior of fibroblasts derived from vulvodynia patients ( Blum et al., 2020 ).…”
Section: Immune Responses To Common Environmental Toxins May Trigger ...mentioning
confidence: 99%
“…Despite these exceptions, as shown in multiple pre-clinical studies of vulvodynia discussed above (Arriaga-Gomez et al, 2019;Kline et al, 2020;Awad-Igbaria et al, 2022), therapies that reduced mast cell accumulation and activation also abrogated vulvar pain. Falsetta and colleagues found that injecting exogenous pro-resolving mediators reduced prostaglandin E2 production in fibroblasts from vulvodynia biopsies (Falsetta et al, 2021).…”
Section: Innate Immune Cells and Mediators Yield New Targets And Stra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation-based models, where vulvodynia is induced using agents such as Candida, zymosan, and Complete Freund's Adjuvant (CFA), highlighting the role of inflammatory processes in the development of vulvodynia [1,[11][12][13][14][15][16][17][18]]. 2.…”
Section: Introductionmentioning
confidence: 99%
“…Allergy-induced models, which utilize allergic reactions to substances like oxazolone (OX) or methylisothiazolinone (MI) to mimic the condition, shedding light on the potential involvement of allergic responses in vulvodynia [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%